PDF Archive

Easily share your PDF documents with your contacts, on the Web and Social Networks.

Share a file Manage my documents Convert Recover PDF Search Help Contact



Solutions ME 342 .pdf


Original filename: Solutions_ME_342.pdf

This PDF 1.6 document has been generated by Adobe Acrobat 7.0 / Adobe Acrobat 7.0 Paper Capture Plug-in, and has been sent on pdf-archive.com on 31/03/2014 at 20:19, from IP address 87.109.x.x. The current document download page has been viewed 691 times.
File size: 69.9 MB (200 pages).
Privacy: public file




Download original PDF file









Document preview


Solutions t o B Problems

CHAPTER 2
B-2-1.
Note that

&rtj =

+S

R e f erring to Egua tion (2-2 1, we obtain

Note t h a t

3 sin (5t

+

45 ") = 3 sin 5t cos 45'

-- - 3

Jz

So we have

fl

-+ 3

cos

s i n 5t + 3 cos 5t

5t sin 45'

Note that

Referring to Equation (2-21, we obtain

f(t) =

B-24.

t <U

0

=cos2Wtros3LLIt

t 1 0

Noting that
cos 2 W t cos 3wt = + ( m s 5 d t + c Q s & J t )
w e have

F(S)

B-2-5.

=

L [ f ( t =) ~

~ + r tn s r ~ t ) ]

[%ms 5

The function f I t ) can be written as

f(t) = (h

- a)

l(t

- a)

The Laplace transform of f(t) is
~ ( s =)

[~(t)] =

J [(t - a )

~ ( -t a)] =

+
-as

6

B-2-6.
-

- a)

f[t) = c l[t

- c I(t

- b)

The Laplace transform oE f ( t ) is
~ ( a =
) c

e-a S
- ce-bs - 2 (,-as S
S

S

B-2-7.

The Function f ( t ) can be written as

So the Laplace transform of f ( t ) becomes

As

a approacl~eszero, t h e l i m i t i n g value of F(s ) becomes as follows:
F ( s ) = lim
ad0
a+O

lim

= lim

= lirn
a+O

B-2-8.

10

- 12.5

e-(a/5)s

+

2 5 =-as

a 2s

da

( 2 . 5 e-(a/5)s

-0.5 s e-(a/5)s
2

The function f(t) can be w r i t t e n as

So the Laplace transform of f(t) becomes

+

2 . 5 .-as)

2 . 5 s e-as

The limiting ~ l u 05
e F(s) as a approaches zero is
l i m F(s) = l i r n
ad0

a30

24(1

- as

e-*=
a3s2

3-2-11.

Define
y = x

Thw
y(O+) = $(O+)

The i n i t i a l value of y can be obtained by use of the initial value theorem
as follows:

Since
y(s1

we obtain

B-2-12.

Note that

= J'+[y!t)l

= d;rGct,1

= sX(S)

- x((U)

Referring to Problm A-2-12,

we have

B-2-14.
f ( t ~emst dt =

Referring to Problem A-2-12,

e-st at = 1
0-

we obtain

where

%(s) can thus be written as

and the inverse Laplace transform of Fl(s) is

Cbl

where

FZ(s) can thus be written as

and the inverse Laplace transform of F Is) is
2

me inverse Laplace transform of F (s) is
1

(bl

where

E (s) can thus be written as
2

and the inverse Laplace transform of F,(s)

.

is

L-

i p ) = -3 .-t

+

3 .-2t

B t .-2t

--2 + - + - -2 - - 2 - 5
s + l
s

5
s + L

-

3
s + l

Rre inverse Laplam transform of f ( s ) is

The inverse Lapla-

transform of F(S) is

f { t )=

S ( t ) 'F

2

Hence
f(t) = e-t cos 3t

4-

4t

1 e-t
--

3

sin 3t

+- 5

s

Hence

The inverse Laplace transform of F(s) is

Hence

The inverse Laplace transform of F l s ) is


Related documents


issyll2010 syllabus
handout 1
18i16 ijaet0916969 v6 iss4 1603to1614
automatic control system
over current realys
6i14 ijaet0514348 v6 iss2 613to619


Related keywords